Tetramethylalloxazines as efficient singlet oxygen photosensitizers and potential redox-sensitive agents - Golczak, Anna; Prukała, Dorota; Sikorska, Ewa; Gierszewski, Mateusz; Cherkas, Volodymyr; Kwiatek, Dorota; Kubiak, Adam; Varma, Naisargi; Pędziński, Tomasz; Murphree, Shaun; Cibulka, Radek; Mrówczyńska, Lucyna; et al. (Scientific reports, 2023)
Tetramethylalloxazines (TMeAll) have been found to have a high quantum yield of singlet oxygen generation when used as photosensitizers. Their electronic structure and transition energies (S0 → Si, S0 → Ti, T1 → Ti) were calculated using DFT and TD-DFT methods and compared to experimental absorption spectra. Generally, TMeAll display an energy diagram similar to other derivatives belonging to the alloxazine class of compounds, namely π,π* transitions are accompanied by closely located n,π* transitions. Photophysical data such as quantum yields of fluorescence, fluorescence lifetimes, and nonradiative rate constants were also studied in methanol (MeOH), acetonitrile (ACN), and 1,2-dichloroethane (DCE). The transient absorption spectra were also analyzed. To assess cytotoxicity of new compounds, a hemolytic assay was performed using human red blood cells (RBC) in vitro. Subsequently, fluorescence lifetime imaging experiments (FLIM) were performed on RBC under physiological and oxidative stress conditions alone or in the presence of TMeAll allowing for pinpointing changes caused by those compounds on the intracellular environment of these cells.